Readiness Analysis of Electronic Medical Record System (RME): A Case Study of Secondary Hospitals in Surabaya - Eka Wilda Faida; Pipit Festi Wiliyanarti; Maria Magdalena Dwi Wahyuni (Health and Technology Journal (HTechJ), 2023)
Background: The Indonesian Minister of Health Regulation requires all hospitals to no longer use manual medical records by 2023. Electronic Medical Records (RME) have many benefits and uses, especially in improving the quality of health services related to patient data as one of the Clinical Decision Support (DCS). But in fact, there are still many hospitals that have not used RME according to the rules that have been launched by the government. Objective: Conduct an analysis of hospital readiness in the use of RME in several secondary hospitals in Surabaya, East Java Indonesia. Method: Observational with descriptive study. Samples were randomly drawn at 228 out of a total population of 562. The study used a survey that was analyzed using SPSS. Before calculating readiness, each question item is tested for validity and reliability to determine the feasibility of the instrument. Results: Organizational culture preparation 81.82% (mean 43.42), leadership governance 80.52% (mean 32.09), human resources 66.23% (mean 21.19), infrastructure 75.32% (mean 15.44) with a total readiness of 112.14 in the score category in range I (98-145) which is very ready. Conclusion: Aspects of organizational culture, leadership governance, human resources, and infrastructure as a whole has a highly prepared category.